Study of heavy-light D and B mesons using heavy quark effective theory - Gupta, Pallavi (My University, 2019)
In this thesis, a comprehensive study is carried out to explore the recently observed heavy light charm (D) and bottom (B) mesons. Ever since the discovery of heavy quarks c and b, study of the properties of heavy hadrons drew a special attention. Experiments at LHCb, BaBar, Belle, BESII/III, CLEO, CDF etc are producing many new charm and bottom meson states with high precision that can be relied upon. Therefore, relevant theoretical approaches should be applied to understand these mesons. Various theoretical models like heavy quark effective theory (HQET), potential model, lattice QCD, QCD sum rules etc are available for the study of these D and B mesons. In the past few years, HQET has emerged out as a successful model for studying the properties of heavy mesons. In this thesis, we intend to study the basic properties like masses, strong decays, branching ratios, splittings for the newly observed heavy -light mesons in both charm and bottom sector. By this study we will be able to complete the charm and bottom spectra up to F-wave and P-wave mesons for radial quantum numbers n=1 and n=2 respectively.
Keywords: mesons; effective theory; strong decay width; chiral perturbation theory; bottom mesons